PERANCANGAN KOMUNIKASI VISUAL PROMOSI KUE SURI SEBAGAI MAKANAN KHAS KOTA PALEMBANG - Tata Auliya Hegar; Mukhsin Patriansah; Yosef Yulius (Penerbit dan Percetakan, CV. Picmotiv, 2023)
Abstract: Palembang City is one of the cities that has a lot of cultural history and traditional snacks. As the capital city of South Sumatra, Palembang has traditional food with savory, spicy, fresh to sweet flavors that are not to be missed. In terms of geographical conditions, Palembang City is divided by the Musi River into two large parts called Seberang Ulu and Seberang Ilir. Kue suri is one of the traditional snacks that has been around since the 80s. The main study in this study is focused on identification, analysis and design on the design work of pacakaging suri cakes, and other supporting media. This Promotion design uses the main media, pre-media, and other design methods. The data is then identified and analyzed using the Design Thinking method which is interpreted according to the text and context. Design Visual communication of suri cakes as a typical snack of Palembang City which is part of this design discussion. This design aims to invite teenagers and the people of Palembang City to preserve the local wisdom of this Palembang City suri cake.